A internet como ferramenta de mediação no acervo artístico-cultural dos Palácios do Governo do Estado de São Paulo - Ferreira, Carolina Daffara [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This research focuses on methods and strategies for educational-based digital tools, aimed at the public school. Thus, we present possibilities, and the main actions of the national museum institutions in several online educational services that exemplify some forms of virtual mediation in order to verify the relevance of using these tools. The study discusses the need for museums to follow the advance of new technologies to engage and retain the public school, consisting of a highly connected generation with new technologies. It also brings a brief overview of the evolution of the museum in the Western world and presents the formation and nature of art collections that comprise the Artistic-Cultural Collection of the Governmental Palaces of the State of São Paulo, focusing on the management policy of each period, highlighting the educational program and the relationship with the website. As a practical exercise, the research presented suggests applying a form of mediation for the virtual site of Artistic-Cultural Collection of the Governmental Palaces to extend relations sector educational institution for the virtual context
Keywords: Acervo Artístico-Cultural dos Palácios do Governo do Estado de São Paulo; Arte e educação; Internet; Mediação; Museus - Aspectos educacionais